Internet usage patterns among medical interns of Muzaffarnagar: A comprehensive survey analysis - Davey, Sanjeev; Raghav, Santosh Kumar; Davey, Anuradha; Singh, Nirankar; Singh, J. V. (Asian Journal of Medical Sciences, 2014)
Introduction: In MBBS completion, Internship period is often having a relatively free time after their duty hours, which is nowadays is being more diverted to spending time online on internet, consequently their usage pattern justifies the study in this area in Indian scenario. Materials and Methods: A prospective cross-sectional survey was carried out on all MBBS medical Interns of 2009 batch attending department of Community Medicine every month(10 Interns/month-total=100) of a Private medical College-Muzaffarnagar. They were first enlisted and their permission for participation and consent in the study were sought, followed by ethical approval of higher authorities of Institution was taken from 1st July 2013 to 1st July 14. A pre-tested semi-structured questionnaire was e-mailed to collect data from medical interns and data analysis was done using Epi-info software version 7.1.3.3. Results: The mode of assessment of Internet by Interns was primarily through Smartphone's (60%), in which Google search & Facebook were used in maximum(69% & 75%). Although difference between impact of Internet on daily and professional life of interns was highly statistically significant (X2= 16.82,d.f=1,p<0.001) but we found, there was no association between monthly amount spent on internet and number of hours spent on Internet (X2=0.74, df=1,p>0.05). 55% of interns used internet > 100 hours in a month. Conclusion: Internet is significantly impacting the daily and professional life of Interns; so they need counseling services from department of Community medicine and Psychiatry in order to regulate Internet use, which can be further clarified from more in-depth studies in future. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10754 Asian Journal of Medical Sciences Vol.6(2) 2015 99-104